2019
DOI: 10.1088/1361-648x/ab27b0
|View full text |Cite
|
Sign up to set email alerts
|

Isovalent substitution effects on thermoelectric transport properties of CoSbX (X  =  S, Se, Te) system

Abstract: We demonstrate a transition of the thermoelectric transport characteristics in the CoSbX (X = S, Se or Te) systems from a p -type semiconductor to metallic conductor with increasing size of the X constituent. From DFT calculations CoSbS is found as an indirect semiconductor with band-gap of 0.38 eV, while both CoSbSe and CoSbTe appear as metals. For the two metals, the calculations reveal two degenerate electron pockets (located near the U point for CoSbSe and near the T point for CoSbTe) and a hole pocket alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Previous density functional theory (DFT) calculations revealed that CoSbTe crystallizes in the Pnn 2 space group and exhibits a semimetal band structure. 55 Therefore, Te alloying in CoSbS would decrease the bandgap accordingly (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Previous density functional theory (DFT) calculations revealed that CoSbTe crystallizes in the Pnn 2 space group and exhibits a semimetal band structure. 55 Therefore, Te alloying in CoSbS would decrease the bandgap accordingly (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Fibre bundle samples were characterized for the phase purity and crystal structure by X-ray diffraction (XRD; PANalytical X'Pert PRO MPD Alpha-1; Cu Kα1 radiation). 39 The relative crystallinity index was computed using an amorphous fitting method 40 applied to the scattering angle range of 13–50°. The crystalline part of the fibre bundle is modelled by using 20 Gaussian functions in the positions defined by the cellulose I beta crystal reflections (these gaussian peaks can be seen in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Topological insulators are recognized as the promising thermoelectric materials, where the tuning of carrier concentration and the intricate phonon scattering are proposed through the intrinsic or artificial manipulations. For example, the increase in the density of states, creating the defects and the interfaces have been manipulated for improving the thermoelectric properties [14][15][16][17][18][19][20][21][22]. Recently, the binary Sb 2 Te 3 has attracted special attention, when it has been identified as a three-dimensional (3D) topological insulator [23,24].…”
Section: Introductionmentioning
confidence: 99%